KALIMAT EFEKTIF RAGAM LISAN KHUTBAH JUMAT DI MASJID JABAL RAHMAH KECAMATAN LANGKAPURA - Anggraini, Nani (LPPM STKIP PGRI Bandar Lampung, 2020)
Abstract: This study aims to identify and describe the use of effective sentences in Indonesian in the Friday sermon at the Jabal Rahma Mosque, Langkapura Sub-district. The method used in this research is descriptive method. Data collection using recording techniques and interviews, the data collected is then analyzed. The content of the sermon is analyzed based on parallels, firmness, frugality, accuracy, cohesiveness, and logic of the sentences in the Friday sermon. The steps taken in analyzing Friday sermons are by transcribing the content of the sermon into written language and identifying sentences in Friday sermons. The results showed that it was less effective than usage